2020
DOI: 10.3389/fpsyg.2020.565688
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study on the Emotional Impact Cause by the COVID-19 Pandemic Quarantine on General Population

Abstract: COVID-19 pandemic represents, not only a public physical health emergency, but a mental health serious problem as well. However, little is known about the psychological impact of the quarantine during this pandemic. The aim of this study is to assess the emotional impact of the lockdown measures imposed by the Argentinian government to fight the virus. For this, a survey was distributed on social network. We surveyed the Argentinian general population twice: 2 days after the mandatory quarantine started (time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
170
4
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 34 publications
(56 reference statements)
17
170
4
6
Order By: Relevance
“…In the USA, a national representative study conducted during an acute period of COVID-19 spread found increased symptoms of anxiety and depression over time, and estimated that, in the most affected states, each day past since March 10 implied an 11% greater chance of moving to the next category of distress (e.g., moving from mild to moderate symptoms) [9]. These kind of effects of the pandemic have been reported by several other countries, including in Latin America, where contagion started later than in Europe and North America [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the USA, a national representative study conducted during an acute period of COVID-19 spread found increased symptoms of anxiety and depression over time, and estimated that, in the most affected states, each day past since March 10 implied an 11% greater chance of moving to the next category of distress (e.g., moving from mild to moderate symptoms) [9]. These kind of effects of the pandemic have been reported by several other countries, including in Latin America, where contagion started later than in Europe and North America [10][11][12].…”
Section: Introductionmentioning
confidence: 83%
“…To plan psychological interventions targeting promotion of, and/or restoration of, mental health we need studies aiming at identifying populations at risk in terms of psychological distress, as well as studies focusing how people experience the life-threating situation. Worldwide, cohort studies identified psychological distress in general population [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Some surveys targeted the mental health of a specific population, such as healthcare workers, students, vulnerable populations, and workers of impacted economic areas [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased screen use behaviors may further be problematic, as subgroups of especially vulnerable individuals may be at risk of developing chronic and excessive usage patterns. Previous research showed that such behaviors relate to poorer psychological and physical well-being ( 3 , 15 , 24 , 25 ). Additionally, these behaviors may become addictive over time, so that several researchers argued that addiction-related disorders need special attention during the COVID-19 pandemic ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such excessive screen use behaviors can be associated with negative effects on psychological well-being during COVID-19-related confinements: students were negatively affected in their sleep quality, sleep duration, physical well-being, and mental health by excessive screen time ( 15 ); increased social media use was associated with a greater tendency to be diagnosed with depression or anxiety ( 24 ); finally, more time consuming news led to higher levels of anxiety and stress ( 3 , 25 ). Moreover, individuals during adolescence and young adulthood may be especially vulnerable to develop excessive, impulsive–compulsive screen use behaviors corresponding to the concept of “behavioral addiction” ( 11 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…This new and unprecedented crisis has affected public moods and behavior. Changes in daily routines, social distancing, partial or complete isolation and the existing health risks lead to emotional distress (Canet-Juric et al 2020;Ćosić et al 2020;Duszyński et al 2020;Heitzman 2020).…”
Section: Introductionmentioning
confidence: 99%